HIDEF: a Data Exchange Format for Information Collected in Honeypots and Honeynets - Hoepers, Cristine; Vijaykumar, Nandamudi L.; Montes, Antonio (INFOCOMP Journal of Computer Science, 2008)
The deployment of honeypots is one of the methods used to collect data about attack trends in computer networks. The lack of a standard format for data representation makes the exchange and centralization of data generated by different technologies difficult. This also restricts the correlation and analysis of this information. This paper presents the HIDEF (Honeypots Information and Data Exchange Format), a proposal for a format to enable the representation and exchange of data and information produced by organizations using honeypots and honeynets